Effectiveness of corncob-based activated carbon bioadsorbent for reducing iron and bromate levels in mineral water using a continuous method - Alfiyatun, Riza; Kristianingrum, Susila (Jurnal Penelitian Saintek, 2025)
This study aims to determine the characteristics of activated carbon made from corn cobs and its effectiveness as a bioadsorbent in reducing iron and bromate levels in bottled drinking water (AMDK). The carbon was activated using 5% HCl and applied in a continuous column system, where the water flowed by gravity. Variations in adsorbent mass and flow rate were used to observe their influence on adsorption efficiency. Characterization results showed that the corn cob activated carbon met the SNI 06-3730-1995 standard, with a moisture content of 3.62%, ash 0.94%, volatile matter 5.9%, and pure activated carbon 89.8%. The optimum adsorbent mass was 1.3 grams, resulting in a decrease in iron levels from 5 mg/L to 0.0155 mg/L, and bromate from 0.08373 mg/L to 0.0015 mg/L"”both within the limits set by SNI 3553-2015. The removal efficiency (Ep) reached 99.69% for iron ions and 97.61% for bromate at a flow rate of 0.2 mL/min and a contact time of 120 minutes. The column method proved effective for filtering bottled drinking water.